HUBUNGAN TINGKAT STRES DENGAN KEJADIAN DISMENORE PRIMER PADA REMAJA DI KABUPATEN PONOROGO, INDONESIA: STUDI CROSS-SECTIONAL : The Correlation between Stress Level and Primary Dysmenorrhea on Adolescents in Ponorogo District, Indonesia: A Cross-Sectional Study - Elok Dwi Sulistiani; Ruri Kharisma Fitriani; Annisa Intan Kholifatullah; Miranda Feyza Nur Imania; Lutfi Agus Salim (Journal of Community Mental Health and Public Policy, 2023)
ABSTRACT Background: Adolescents generally experience difficulties adapting to secondary changes, especially female adolescents. This causes female adolescents to experience higher levels of stress. The stress experienced can have an impact on health, such as primary dysmenorrhea. Purpose: The purpose of this research was to analyze the relationship between stress levels and primary dysmenorrhea that occurs on female adolescents in Ponorogo District. Methods: The method used in this research was a quantitative approach, with the type of analytic observational and cross-sectional research. Result: Respondents’ stress levels were mostly in the normal category, with 31 respondents (32%), while primary dysmenorrhea was dominated by moderate pain, with 50 respondents (51.5%). Spearman Rank Test resulted in a p-value of 0.000 with a correlation coefficient test value of 0.392, which means that there was a weak significant relationship between stress and dysmenorrhea. Conclusion: It can be concluded that in Ponorogo District, the primary dysmenorrhea experienced was in the moderate pain category, and the stress level was in the normal category, with the test results showing that there was a weak relationship between stress levels and primary dysmenorrhea. ABSTRAKLatar Belakang: Remaja umumnya mengalami kesulitan dalam beradaptasi dengan perubahan sekunder, terutama remaja perempuan. Hal ini menyebabkan remaja perempuan mengalami tingkat stres yang lebih tinggi. Stres yang dialami dapat berdampak pada kesehatan, yaitu mengakibatkan dismenore primer. Tujuan: Dilakukan penelitian untuk menganalisis hubungan tingkat stres dengan dismenore primer yang terjadi pada remaja perempuan di Kabupaten Ponorogo. Metode: Metode yang digunakan di dalam penelitian yaitu, pendekatan kuantitatif dengan jenis penelitian observasional analitik dan cross sectional menjadi desain penelitian ini. Hasil: Tingkat stres responden paling banyak terdapat pada kategori normal sejumlah 31 responden (32%), sedangkan pada dismenore primer didominasi nyeri sedang sejumlah 50 responden (51,6%). Hasil uji statistik menggunakan Uji Spearman Rank menghasilkan p-value 0,000<0,05 dengan nilai uji koefisien korelasi sebesar 0,392 yang berarti terdapat hubungan bermakna yang lemah antara stress dan dismenore primer. Kesimpulan: Dapat diambil kesimpulan bahwa di Kabupaten Ponorogo dismenore primer yang dialami berada pada kategori nyeri sedang dan tingkat stres ada pada kategori normal dan terdapat hubungan yang lemah antara tingkat stres dan dismenore primer.